2022
DOI: 10.1002/job.2585
|View full text |Cite
|
Sign up to set email alerts
|

Intimate partner aggression and work: An interdisciplinary review and agenda for future research

Abstract: Intimate partner aggression (IPA) is a social issue that affects the workplace. While IPA has been relatively ignored by management scholars due to notions that it is a private domestic matter, recent research offers mounting evidence of its spillover effects at work, including consequences for victims, perpetrators, coworkers, and organizations. To date, scholarly research on IPA and work has been impeded because existing research is scattered across disciplines with differing conceptualizations and emphasis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 225 publications
(256 reference statements)
0
8
0
Order By: Relevance
“…Research on the role of organizations in mitigating domestic violence—which is more egregious than partner-instigated incivility—has noted that organizations can implement policies to help curtail domestic violence, including offering flexible work arrangements to limit exposure to hostile exchanges (Wilcox et al, 2021). Other work has suggested that supervisor and coworker social support are important in alleviating the spillover of mistreatment at home (in the form of intimate partner aggression) into the workplace (Deen et al, 2022; O’Leary-Kelly et al, 2008; Tolentino et al, 2017). Thus, although our focus was on how perspective taking can help alleviate the extent to which partner-instigated incivility affects employees, prior scholarship still suggests that organizational support is likely to be impactful in this context.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research on the role of organizations in mitigating domestic violence—which is more egregious than partner-instigated incivility—has noted that organizations can implement policies to help curtail domestic violence, including offering flexible work arrangements to limit exposure to hostile exchanges (Wilcox et al, 2021). Other work has suggested that supervisor and coworker social support are important in alleviating the spillover of mistreatment at home (in the form of intimate partner aggression) into the workplace (Deen et al, 2022; O’Leary-Kelly et al, 2008; Tolentino et al, 2017). Thus, although our focus was on how perspective taking can help alleviate the extent to which partner-instigated incivility affects employees, prior scholarship still suggests that organizational support is likely to be impactful in this context.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, our article focused on how employees coped with one specific type of negative family interaction-partner-instigated incivility. However, other forms of mistreatment at home exist, including intimate partner violence (Deen et al, 2022) and family undermining (Hoobler & Brass, 2006). Much like the diversity of mistreatment events employees may experience at work (Hershcovis, 2011), the characteristics distinguishing how employees respond to types of family mistreatment and their downstream effects may vary between types of partner mistreatment.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the positive influence of an intimate partner might be beneficial in maintaining one's determination, managing work–family conflict and engaging efficiently at work (Bermele et al, 2018 ). In contrast, the negative impact of an intimate partner creates poor attention at work (Anderson et al, 2018 ), job burnout and dissatisfaction, which lessens job interest and makes it more challenging to continue the job (Deen et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent research evidence suggests that IPV negatively impacts organizations and their employees in a variety of ways (e.g., Deen et al, 2021;Duffy et al, 2004;LeBlanc et al, 2014;Tolentino et al, 2016; for a comprehensive review, see Deen et al, 2022). At the organizational level, IPV has been found to incur direct (e.g., illness, death, absenteeism, and turnover), indirect (e.g., reduced commitment, morale, and performance), and intangible costs (e.g., negative impact on company image and work climate; O' Leary-Kelly et al, 2008) for organizations.…”
mentioning
confidence: 99%